IR ABSORPTION SPECTRA OF VITREOUS SILICA AND SILICATE GLASSES: THE NATURE OF BANDS IN THE 1300 TO 5000 CM- 1 REGION - Efimov A.M.; Pogareva V.G. (My University, 2006)
The transmittance spectra of Types I and III silica glasses in the 1300 to 5000 cm- 1 region are measured and the absorptivity spectra calculated from data obtained are processed with the dispersion analysis method based on the convolution model for the complex dielectric function. The IR absorption bands with inherent frequencies around 1480, 1630, 1760, 1870, 1980, 2140, 2260, 2370, 2540, 2660, and 2810 cm- 1 in the spectra of glasses of both types are shown to be due to the combination modes and overtones of the silica matrix; the same is assumed for a weak 3140 cm- 1 band. A weak band with frequency around 3490 cm- 1 is assigned tentatively to the symmetric stretching mode of interstitial H2O molecules present in trace amounts. For Type III glass, nine other water-related bands are found. Of these, three bands with frequencies from 3570 to 3675 cm- 1 are assigned to the stretching modes of hydroxyl groups in two different structural sites and the remaining six bands with frequencies from ~3750 to ~4510 cm- 1 are assigned to unidentified combination modes involving certain stretching vibrations of hydroxyl groups. Data obtained are compared to recent data on the IR band parameters of Na2O-SiO2, K2O-CaO-BaO-SiO2 and window glasses. Bands around 1540-1610, 1670-1750, 1810-1840, 1900-1930, and 2030-2110 cm- 1 in the spectra of these glasses are concluded to be envelopes, each of the envelopes covering a hydroxyl-related band and a band or two due to certain combination modes or overtones of glass matrices. © 2006 Elsevier B.V. All rights reserved.
Keywords: DATA PROCESSING; DIELECTRIC FUNCTION; GLASSES; IR SPECTRA; WATER